2020
DOI: 10.1002/cbic.201900665
|View full text |Cite
|
Sign up to set email alerts
|

Phototemtide A, a Cyclic Lipopeptide Heterologously Expressed from Photorhabdus temperata Meg1, Shows Selective Antiprotozoal Activity

Abstract: A new cyclic lipopeptide, phototemtide A (1), was isolated from Escherichia coli expressing the biosynthetic gene cluster pttABC from Photorhabdus temperata Meg1. The structure of 1 was elucidated by HR‐ESI‐MS and NMR experiments. The absolute configurations of amino acids and 3‐hydroxyoctanoic acid in 1 were determined by using the advanced Marfey's method and comparison after total synthesis of 1, respectively. Additionally, three new minor derivatives, phototemtides B–D (2–4), were identified by detailed HP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 41 publications
1
15
0
Order By: Relevance
“…Lipopeptides are a diverse class of molecules containing a nonpolar fatty acid chain and amino acid residues of varying length and hydrophobicity. Many bacterial lipopeptides originate from NRPSs. , These amphiphilic molecules display a variety of bioactivities from antimicrobial, to surfactant, to cell signaling . Most antimicrobial lipopeptides are macrocyclic; however, there are also several reports of linear lipopeptides with bioactivities such as paenipeptin (antibacterial) and holrhizin A (surfactant) .…”
Section: Resultsmentioning
confidence: 99%
“…Lipopeptides are a diverse class of molecules containing a nonpolar fatty acid chain and amino acid residues of varying length and hydrophobicity. Many bacterial lipopeptides originate from NRPSs. , These amphiphilic molecules display a variety of bioactivities from antimicrobial, to surfactant, to cell signaling . Most antimicrobial lipopeptides are macrocyclic; however, there are also several reports of linear lipopeptides with bioactivities such as paenipeptin (antibacterial) and holrhizin A (surfactant) .…”
Section: Resultsmentioning
confidence: 99%
“…To defend this from colonization by microbial competitors, a broad spectrum of antimicrobials is produced. These include antifungals: biocornutin ( Böszörményi et al, 2009 ), cabanillasin ( Houard et al, 2013 ), EP-19, GP-20 ( Xiao et al, 2012 ), and xenocoumacin ( Yang et al, 2011 ); antibacterials: darobactin ( Imai et al, 2019 ), xenematide ( Lang et al, 2008 ), photoditritide ( Zhao et al, 2019 ), xenobactin ( Grundmann et al, 2013 ), odilorhabdins ( Pantel et al, 2018 ), xenorhabdin ( McInerney et al, 1991 ), and PAX peptides ( Gualtieri et al, 2009 ); antiprotozoals: phototemtide ( Zhao et al, 2020 ), szentiamide ( Ohlendorf et al, 2011 ), chaiyaphumins ( Grundmann et al, 2014 ), rhabdopeptide/xenortide-like peptides (RXP) ( Zhao L. et al, 2018 ), xenortide ( Reimer et al, 2014 ), xenoamicin ( Zhou et al, 2013 ), and ambactin ( Schimming et al, 2014 ); and cytotoxic agents: fabclavines ( Wenski et al, 2020 ) and phenylethylamine (PEA) derivatives ( Proschak et al, 2011 ).…”
Section: The Nematode-bacterium Lifecycle and Bacterial Biomoleculesmentioning
confidence: 99%
“…This new cyclic lipopeptide has three more minor derivatives. It has been reported that this peptide has weak antiprotozoal activity with IC 50 = 9.8 μM, against deadly plasmodium species Plasmodium falciparum ( Zhao et al, 2020 ). New peptide drugs have gained attention due to their easy synthesis, low toxicity, fewer side effects, and rapid elimination ( Du et al, 2015 ).…”
Section: Photorhabdus As Source Of Antiprotozoal Compoundsmentioning
confidence: 99%